2009
DOI: 10.1017/s0266462309090072
|View full text |Cite
|
Sign up to set email alerts
|

Finding legitimacy for the role of budget impact in drug reimbursement decisions

Abstract: Objectives: Research has shown that effectiveness, cost-effectiveness, and severity of illness each play a role in drug reimbursement decisions. However, the role of budget impact in such decisions is less obvious. Policy makers almost always demand a budget impact estimate yet seem reluctant to formally include budget impact as a rationing criterion. Health economists even reject budget impact as a legitimate criterion. For these reasons, it is important to examine its use in rationing decisions, and rational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 33 publications
3
31
0
2
Order By: Relevance
“…This combined background is crucial, because it answers fundamental questions of whether a health technology presents a value for the money and what resources will eventually be necessary to implement this decision (22,23). The actual implementation of these and other efficiency criteria is, however, very often unclear and non-transparent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This combined background is crucial, because it answers fundamental questions of whether a health technology presents a value for the money and what resources will eventually be necessary to implement this decision (22,23). The actual implementation of these and other efficiency criteria is, however, very often unclear and non-transparent.…”
Section: Discussionmentioning
confidence: 99%
“…This problem is highlighted even in countries where credibility and accountability have long been established as a mandatory requirement in public health decision-making (24). Niezen et al (23) concluded that despite the fact that regulators almost always demand a budget impact estimate, they seem reluctant to formally include it as a rationing criterion. Budget impact is believed to be lacking scientific rigor, thus not representing a rational use of evidence-based and explicit knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…There has been growing interest in BIA recently 4 and Health Technology Assessment (HTA) agencies in several countries request BIA to support decision making processes on the adoption of health technology innovations 5,6,7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, many insurers require manufacturers to provide "budget impact assessments" whose main purpose appears to be to limit expenditure on those drugs anticipated to have a large total cost. (25) An expenditure cap appears to work against the incentives created by VBP, since it limits the upside of the manufacturer and thus reduces the motivation to develop the therapies with the greatest potential to improve population health. Nevertheless, an expenditure cap may still be optimal to reduce investment in innovation.…”
Section: Expenditure Capsmentioning
confidence: 99%